Directions in entrepreneurship education in Europe - Rizza, C. (2011)
An extraordinary proliferation of entrepreneurship courses and programs was and still is underway in colleges and universities worldwide. In Europe this phenomenon has been further stimulated by the focus on Entrepreneurship as key objective for the implementation of the Europe2020 strategy (EC, 2010). This paper provides a systematized overview of patterns and directions in EE in Europe in recent years. We conduct a review of the published research of the theme with an European focus in an attempt to organize the literature along precise lines. When possible we use empirical findings to sustain our arguments. Systematizing the existing literature is a necessary step in developing the field. For researchers, this overview will be constructive in providing an analysis of the directions of published research and in setting up a research agenda for the future. It also raises awareness with regard to entrepreneurship, and in particular, to its potential contribution to the individuals and to the competitiveness of economies. The empirical analysis adds to our knowledge about the current situation of EE in practice in Europe.